The land before time II the great valley adventure - Bennett, Jeff.; Hogan, Heather, 1949-; Smith, Roy Allen; MCA Universal Home Video (Firm) (Universal City, Calif. : MCA Universal Home Video, 1994)
Littlefoot, a young brontosaurus, and his friends Cera, Spike, Ducky and Petrie travel to the forbidden "Great beyond", where they soon find themselves in big trouble!
Rated G.
Closed captioned for the hearing impaired.
"82142"--Container.
Stock number from the cassette label or/and box
Producer-director, Roy Allen Smith ; co-producer, Zahra Dowlatabadi ; animation producer, Nelson Shin ; screenplay, Dev Ross, John Loy & John Ludin ; based on characters created by Judy Freudberg & Tony Geiss ; music, Michael Tavera ; original "Land before time" score by James Horner.
Voices: Jeff Bennett, Heather Hogan, Tress MacNeille, Rob Paulsen, Linda Gary, Candace Hutson, Kenneth Mars, Scott McAfee, John Ingle, narrator.
Keywords: Dinosaurs -- Juvenile drama; Animated films; Films for the hearing impaired; Dinosaurs -- Drama